Effect of Free Fatty Acid Pretreatment to Yield, Composition and Activation Energy in Chemical Synthesis of Fatty Acid Methyl Ester - Nor Saadah Mohd Alias; Harumi Veny; Fazlena Hamzah; Noorhaliza Aziz (Universitas Gadjah Mada, 2019)
Transesterification of waste cooking oil (WCO) for fatty acid methyl ester synthesis using calcium oxide (CaO) as a catalyst with absence and presence of free fatty acid (FFA) pretreatment (untreated and pretreated) prior to reaction have been investigated. The preliminary study was started from theoretical stoichiometric amount molar ratio of methanol to oil. This preliminary experiment showed that indeed, in transesterification with the chemical catalyst the molar ratio of methanol to oil should be exceeding the theoretical stoichiometric molar ratio, due to the fast reversible reaction. The highest FAME content of 81% was achieved at a temperature of 75 °C with pretreated FFA. The composition of methyl ester with pretreated FFA was affected by temperature, where increasing temperature leads to increasing of methyl oleate as major methyl ester in the product. The relation of temperature dependence was further studied by Arrhenius law correlation. It is shown that activation energy was affected by pretreatment of fatty acid. The activation energy (Ea) of transesterification with untreated and pretreated free fatty acid were found as ± 16 kJ/mol and ± 68 kJ/mol, respectively. Unlike untreated FFA, the Ea of transesterification with pretreated FFA was within the range of activation energy for transesterification for the base catalyst. This study showed that methyl ester synthesis was best obtained when FFA was pretreated prior to transesterification. In addition, WCO is a potential feedstock for biodiesel production since it is biodegradable, economic, environmentally friendly and abundantly available.